Association Between Menopause and Metabolic Syndrome in the Registration Phase Data of Tabari Cohort Population - Seyed-Robabe Babaei; Mahmood Moosazadeh; Motahareh Kheradmand; Amirsaeed Hosseini; Masoumeh Bagheri-Nesami (علوم بهداشتی ایران, 2025)
Background and Purpose: Metabolic syndrome is a multifactorial condition closely related to cardiovascular diseases and diabetes. Hormonal changes during menopause make women prone to metabolic syndrome. This study investigated the relationship between menopause and metabolic syndrome in the data registration phase of the Tabari cohort population. Materials and Methods: The present study is a cross-sectional study conducted within the framework of the Tabari cohort study (part of the national cohort studies titled “prospective epidemiological studies in Iran”) using data collected in the study’s first phase. The samples consist of 6106 women aged 35-70 who were selected via the census method between June 2015 and November 2017. Women who reported menopause and met the diagnostic criteria for metabolic syndrome based on the adult treatment panel III (ATP III) were included in this study. Descriptive statistics were employed to describe the variables and the chi-square test and logistic regression were used to analyze the association between two qualitative variables. SPSS software, version 21 was used for data analysis. P≤0.05 was also considered significant. Results: Post-menopausal women were 1.46 times more at risk of metabolic syndrome than pre-menopausal women (P=0.001). Women aged 55 years and older had 1.39 times more chance of developing metabolic syndrome than women younger than 40 years. Conclusion: Menopause and post-menopause age had a significant relationship with metabolic syndrome. Therefore, it is necessary to make plans to increase women’s awareness and change their lifestyle and health levels during menopause.